ENDOGENOUS TECHNOLOGICAL PROGRESS AND ECONOMIC GROWTH IN A MODEL WITH NATURAL RESOURCES - Malaczewski, Maciej (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
Idea of technological progress based on two different types of research that generate radical and incremental innovations, became new approach in endogenous growth modeling. This approach seems to be useful in modeling relationships between technological progress, natural resources, environmental quality and economic growth. The purpose of this paper is to answer questions about relationships between long-term economic growth, technological progress and use of natural resources. The main object is an impact of natural resources use on growth rate and a role of endogenous technological progress.